Controle circadiano e homeostático do sono-vigília em pacientes com acidente vascular encefálico e correlações com a qualidade de vida e o nível de atividade física - Cavalcanti, Paula Regina Aguiar (2009)
The cerebral vascular accident is a neurological dysfunction of vascular origin that leds to development of motor sensibility, cognitive, perceptive and language deficits. Despite the fact that the main sleep disorders in stroke patients are well known, it is still necessary to analyze which mechanisms of regulation of sleep and wakefulness are affected. The objective of this study was to evaluate the changes in the circadian and homeostatic control of sleep-wakefulness in stroke patients and the correlations with quality of life and level of physical activity. The study analyzed 22 stroke patients (55± 12 years old) and 24 healthy subjects (57 ±11 years old). The instruments used in this study were questionnaires on sleep quality, daytime sleepiness, quality of life, physical activity level and the actigraphy. The data were analyzed using the Student `t test, Mann-Whitney test, ANOVA and Spearman's correlation tests. The results showed stability in the sleep-wake circadian expression with changes in the amplitude of the rhythm. However, significant changes were found related to the homeostatic component characterized by increased sleep duration, increased latency, fragmented sleep and lower sleep efficiency. Additional data showed decreased quality of sleep and increased daytime sleepiness, as well as decreased quality of life and level of physical activity. The results indicate that the interaction of circadian and homeostatic control of sleep-wake is compromised and the main reason might be because of the homeostatic component and the lower activity level resulting from the brain damage. Thus, further studies may be developed to evaluate whether behavioral interventions such as increased daytime activity and restriction of sleep during the day can influence the homeostatic process and its relation to circadian component, resulting in improved quality of nocturnal sleep in stroke patients